The Roles of Age, Attitude, and Use in First Language Development and Attrition of Turkish–English Bilinguals. (17th June 2019) - Schmid, Monika S.; Karayayla, Tuğba
Abstract: Recent decades have seen an increase in research informing our understanding of the complex ways in which bilingual development is shaped by biological, cognitive, and behavioral factors. We investigate the predictors that shape, drive, and constrain the development of the first language (L1) of bilinguals, focusing on 92 Turkish–English bilingual adults with a wide range (0–42) of age at onset (AaO). We tested their productive command of L1 lexical, morphological, and syntactic features, investigating to what extent background variables relating to AaO, experience, and attitudes toward the Turkish language and culture predict the relative level of proficiency across these features. To obtain a comprehensive picture of the interaction of these linguistic and extralinguistic factors, we employed structural equation modeling. We show that for speakers with younger AaOs, exposure‐related factors are associated with the level of L1 proficiency they retain as adults; for later bilinguals, exposure‐related factors matter less. Abstract :